The emerging role of synaptic cell-adhesion pathways in the pathogenesis of autism spectrum disorders - Betancur, Catalina; Sakurai, Takeshi; Buxbaum, Joseph D. (Trends in neurosciences (Regular ed.), 2009)
Recent advances in genetics and genomics have unveiled numerous cases of autism spectrum disorders (ASDs) associated with rare, causal genetic variations. These findings support a novel view of ASDs in which many independent, individually rare genetic variants, each associated with a very high relative risk, together explain a large proportion of ASDs. Although these rare variants impact diverse pathways, there is accumulating evidence that synaptic pathways, including those involving synaptic cell adhesion, are disrupted in some subjects with ASD. These findings provide insights into the pathogenesis of ASDs and enable the development of model systems with construct validity for specific causes of ASDs. In several neurodevelopmental disorders frequently associated with ASD, including fragile X syndrome, Rett syndrome and tuberous sclerosis, animal models have led to the development of new therapeutic approaches, giving rise to optimism with other causes of ASDs.